Digital expression profiling of the compartmentalized translatome of Purkinje neurons - Kratz, Anton; Beguin, Pascal; Kaneko, Megumi; Chimura, Takahiko; Suzuki, Ana Maria; Matsunaga, Atsuko; Kato, Sachi; Bertin, Nicolas; Lassmann, Timo; Vigot, Réjan; Carninci, Piero; Plessy, Charles; et al. (Genome Research, 2014)
Underlying the complexity of the mammalian brain is its network of neuronal connections, but also the molecular networks of signaling pathways, protein interactions, and regulated gene expression within each individual neuron. The diversity and complexity of the spatially intermingled neurons pose a serious challenge to the identification and quantification of single neuron components. To address this challenge, we present a novel approach for the study of the ribosome-associated transcriptome—the translatome—from selected subcellular domains of specific neurons, and apply it to the Purkinje cells (PCs) in the rat cerebellum. We combined microdissection, translating ribosome affinity purification (TRAP) in nontransgenic animals, and quantitative nanoCAGE sequencing to obtain a snapshot of RNAs bound to cytoplasmic or rough endoplasmic reticulum (rER)–associated ribosomes in the PC and its dendrites. This allowed us to discover novel markers of PCs, to determine structural aspects of genes, to find hitherto uncharacterized transcripts, and to quantify biophysically relevant genes of membrane proteins controlling ion homeostasis and neuronal electrical activities.